Define intervention (The Biblical archaeology review, 2020)
What’s the definition of nilotic? 1. seemingly nonexistent 2. relating to the Nile River 3. nocturnal 4. passive, calm 064 Answer: 2 Nilotic is an adjective that denotes a relationship to the Nile River or to the Nile region of Africa, including ancient Cush. Nilotic languages refer to a class of related languages spoken in the region between South Sudan and Tanzania, including the Maasai language spoken in southern Kenya.